Spherical crystalline silica particles, spherical silica particle mixtures and composite materials

Spherical silica particles with a crystalline structure address the limitations of existing fillers by enhancing dielectric and thermal properties, ensuring effective high-frequency signal transmission and thermal management in semiconductor encapsulants and circuit boards.

JP7603584B2Active Publication Date: 2024-12-20NIPPON STEEL CHEM & MATERIAL CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2021521923
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-05-31
Filing Date
2020-06-01
Publication Date
2024-12-20
Estimated Expiration
2040-06-01

AI Technical Summary

Technical Problem

Existing spherical silica fillers and silica-resin composites fail to meet the requirements of high dielectric properties, thermal conductivity, and fluidity necessary for high-frequency signal transmission, leading to issues like signal delay, energy loss, and thermal expansion mismatch in semiconductor encapsulants and circuit boards.

Method used

Development of spherical silica particles with a specific crystalline structure, comprising a total of 60% or more of a crystalline cristobalite and quartz phase, optimized particle size distribution, and high circularity, achieved through heat-treatment of amorphous silica particles at controlled temperatures and aluminum addition, resulting in improved dielectric and thermal properties.

Benefits of technology

The spherical silica particles exhibit low dielectric loss tangent, high thermal conductivity, and excellent fluidity, enabling high filling properties and suitability for high-frequency signal transmission applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007603584000006
    Figure 0007603584000006
  • Figure 0007603584000001
    Figure 0007603584000001
  • Figure 0007603584000002
    Figure 0007603584000002
Patent Text Reader

Abstract

[Problem] To provide: spherical silica particles that have excellent dielectric properties and can have both excellent thermal properties and excellent fluidity; a spherical silica particle mixture; and a composite material. [Solution] Provided are: spherical silica particles characterized by containing at least 60% in total of crystalline cristobalite phase and crystalline quartz phase in which the average size of the polycrystalline grains constituting the crystalline cristobalite phase or quartz phase is 2 μm or more and a dielectric loss tangent at 10 GHz is 0.0020 or less as determined by the cut-off circular waveguide method (JIS R1660-1:2004); a spherical silica particle mixture containing the same; and a composite material.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to spherical crystalline silica particles and a spherical silica particle mixture containing the same, which have excellent dielectric properties and are suitable for use in forming a semiconductor encapsulant for high-frequency signals of 3 GHz or more, and for forming a wiring board, and to a composite material formed by combining the same with a resin. [Background technology]

[0002] The frequency is becoming higher due to the increase in the amount of information caused by the advancement of communication technology and the rapid expansion of the use of millimeter wave bands such as millimeter wave radar. Semiconductors that handle these high frequency signals and circuit boards that transmit them are composed of electrodes and dielectrics that form the circuit patterns. Since suppressing signal propagation delay is important for high-speed signal transmission, a low relative dielectric constant (εr) is required. In addition, to suppress energy loss during signal transmission, the dielectric tangent (tan δ) of the dielectric material must be small. To achieve low dielectric loss, the dielectric material must have low polarity and low dipole moment. In addition to these dielectric properties, when mounting the board, thermal properties such as thermal conductivity and thermal expansion coefficient are important to suppress heat generation from the IC chip and mismatch of thermal expansion with the electrode material, and mechanical properties such as high flexural strength are also important.

[0003] The dielectric materials mainly used are ceramic fillers, resins, and composites made by combining these. In particular, with the recent expansion of use of the millimeter wave band, there is a demand for ceramic fillers and resins with even lower εr and tan δ. Resins have a relatively small εr and are suitable for high frequencies, but their tan δ and thermal expansion coefficient are higher than those of ceramic fillers. For this reason, composites made by combining fillers and resins for the millimeter wave band are suitable for: (1) making the ceramic filler itself low εr and low tan δ, and (2) increasing the ceramic filler loading to reduce the amount of resin with a large tan δ.

[0004] Silica (SiO2) particles have been used as ceramic fillers. If the silica particles have an angular shape, their fluidity, dispersibility, and filling properties in the resin will be poor, and the manufacturing equipment will also wear out. To improve these problems, spherical silica particles are widely used. It is believed that the closer the spherical silica filler is to a perfect sphere, the better its filling properties, fluidity, and mold wear resistance will be, and fillers with a high degree of circularity have been pursued. In addition, further improvements in filling properties have been considered by optimizing the particle size distribution of the filler. However, if the filling rate is increased too much by making the filler spherical and optimizing the particle size distribution, the fluidity of the composite as a sealant will decrease and its moldability will deteriorate. In order to ensure high fluidity, it is difficult to increase the silica filler filling rate to 85 mass% or more, and so it was previously limited to less than 85 mass%.

[0005] Thermal spraying is known as a method for producing spherical silica. In thermal spraying, the raw material, crushed silica particles, are passed through a flame at 2000°C or higher, causing the particles to melt and become spherical due to surface tension. The molten, spherical particles are transported by air currents to prevent them from fusing together, and are then collected, after which the particles are rapidly cooled. Because they are rapidly cooled from a molten state, this silica (fused silica) has an amorphous structure.

[0006] This spherical fused silica is amorphous, so its thermal expansion coefficient and thermal conductivity are low. The thermal expansion coefficient of amorphous silica is 0.5 ppm / K, and its thermal conductivity is 1.4 W / mK. These physical properties are roughly equivalent to the thermal expansion coefficient of quartz glass, which has a non-crystalline (amorphous) structure rather than a crystalline structure. For this reason, mixing it with a resin with a high thermal expansion coefficient has the effect of lowering the thermal expansion of the encapsulant itself. By setting the thermal expansion coefficient of the composite as an encapsulant close to that of silicon, deformation caused by thermal expansion behavior can be suppressed when encapsulating an IC chip.

[0007] However, encapsulants (composites) that are excessively filled with amorphous silica, which has a low thermal expansion coefficient, can have a smaller thermal expansion coefficient than Si, and warping or cracking can occur due to the heating temperature during reflow and the operating temperature of semiconductor devices.In addition, the low thermal conductivity of silica poses a problem with the dissipation of heat generated by semiconductor devices.

[0008] As described above, the properties required for a silica filler compatible with high frequencies of 3 GHz or more are that it must exhibit excellent dielectric properties, as well as satisfy all requirements, such as filling properties, fluidity, thermal properties, mechanical strength performance, and mold abrasion resistance, so that it can be blended in large quantities with a resin and still maintain its performance as a sealing material. However, such a silica filler and silica-resin composite did not exist until now.

[0009] In light of these circumstances, the inventors aimed to provide a ceramic filler (spherical silica particles) with excellent dielectric properties for use in devices and substrates for 5G (fifth generation mobile communication system) with frequencies of 3 GHz or higher, as well as in automotive radars and the like that use millimeter wave bands of 60 GHz or higher. [Prior art documents] [Patent documents]

[0010] [Patent Document 1] International Publication No. 2016 / 031823 [Patent Document 2] International Publication No. 2018 / 186308 Summary of the Invention [Problem to be solved by the invention]

[0011] An object of the present invention is to provide spherical silica particles, a spherical silica particle mixture, and a composite material that have excellent dielectric properties and also have excellent thermal properties and flowability. [Means for solving the problem]

[0012] The present inventors have conducted extensive research aimed at solving the above problems. As a result, they have found that in order to obtain silica particles having excellent dielectric properties such as low dielectric constant and low dielectric loss tangent, and excellent thermal properties such as high thermal conductivity and high thermal expansion coefficient, it is effective to heat-treat spherical fused (amorphous) silica to crystallize it and form it into a specific crystal structure. That is, it has been confirmed for the first time that the spherical silica particles of the present invention have a significantly lower dielectric loss tangent at high frequencies of 3 GHz or more than amorphous silica particles, and also have high thermal conductivity, and thus the present invention has been completed. Effect of the Invention

[0013] The spherical silica particles according to the present invention have a specific crystal structure, and therefore have excellent dielectric properties (low dielectric constant and dielectric tangent), and also exhibit superior thermal properties () compared to conventional spherical crystalline silica particles. In addition, because they are spherical, have a narrow particle size distribution, and can have a high degree of circularity, they achieve both high flowability and high dispersibility and high packing properties, and therefore can be suitably used as a filler in semiconductors, substrates, etc. for transmitting high-frequency signals. [Brief description of the drawings]

[0014] [Figure 1] FIG. 1 is a diagram for explaining calculation of the photographed area and perimeter of a particle. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0015] The present invention provides the following aspects. [1] Spherical silica particles characterized in that they contain a crystalline cristobalite phase and a crystalline quartz phase in total of 60% or more, the average diameter of polycrystalline grains constituting the crystalline cristobalite phase or the quartz phase is 2 μm or more, and the dielectric loss tangent at 10 GHz determined by the cutoff cylindrical waveguide method (JIS R1660-1:2004) is 0.0020 or less. [2] The spherical silica particles according to [1] contain more than 0.5 mass % and not more than 2.0 mass % of aluminum, calculated as an oxide. [3] The spherical silica particles according to [1] or [2], wherein the ratio of the crystalline quartz phase in the spherical silica particles is 30% or more. [4] The spherical silica particles according to any one of [1] to [3], wherein the spherical silica particles have a circularity of 0.83 or more for particles with a particle diameter of 10 μm or more. [5] A spherical silica particle mixture comprising 95% by mass or more and 99.9% by mass or less of the spherical silica particles according to any one of [1] to [4], and 0.1% by mass or more and 5% by mass or less of ultrafine particles having an average particle size of 0.1 μm or less. [6] A composite material comprising a resin containing 85% by mass or more and 95% by mass or less of the spherical silica particles according to any one of [1] to [4].

[0016] Crystal structures of silica (SiO2) include cristobalite, quartz, and tridymite. Silica with these crystal structures has a higher thermal expansion coefficient and thermal conductivity than amorphous silica. Therefore, by replacing fused (amorphous) silica with an appropriate amount of crystalline silica, it is possible to improve thermal conductivity while suppressing the thermal expansion difference with the IC chip. Furthermore, by optimizing the particle size distribution of fused (amorphous) silica and crystalline silica, it is possible to obtain a silica filler (spherical silica particles) that exhibits even higher filling properties.

[0017] The spherical silica particles of the present invention contain a total of 60% or more of a crystalline cristobalite phase and a crystalline quartz phase (hereinafter, collectively referred to as "crystalline phase"). That is, the content of the crystalline phase in the spherical silica particles is 60% or more. If it is 60% or more, excellent dielectric properties are exhibited. Generally, the higher the proportion of crystalline silica, the better the dielectric properties are. Silica other than crystalline silica is amorphous. The crystalline phase may be either a crystalline cristobalite phase or a crystalline quartz phase, or the crystalline cristobalite phase and the crystalline quartz phase may coexist. In addition, the spherical silica particles of the present invention may contain crystalline tridymite in addition to the crystalline cristobalite phase and the crystalline quartz phase.

[0018] The abundance ratio of crystalline phases such as cristobalite and quartz can be measured, for example, by X-ray diffraction (XRD). When measuring by XRD, it can be calculated from the sum of the integrated intensities of the crystalline peaks (Ic) and the integrated intensity of the amorphous halo portion (Ia) using the following formula.

[0019] X (crystal phase ratio) = Ic / (Ic+Ia) x 100 (%)

[0020] The ratio of each crystalline phase in the crystalline phase contained in the spherical silica particles according to the present invention is measured by XRD as described below unless otherwise specified. The ratio of each crystalline phase is calculated by mass ratio from the ratio of the sum of the integrated intensity of each peak using the peak data of PDF 33-1161 for the crystalline quartz phase, PDF 11-695 for the crystalline cristobalite phase, and PDF 18-1170 for the crystalline tridymite phase. In addition, since the peak positions of the maximum intensity derived from the cristobalite phase and the tridymite phase are close to each other, the peaks are separated to calculate the intensity, or the second and subsequent peaks of intensity are corrected based on the intensity ratio of the PDF data and used for calculation.

[0021] The crystalline cristobalite phase and the crystalline quartz phase are composed of many microcrystals, i.e., polycrystalline grains. In the spherical silica particles of the present invention, the average diameter of the polycrystalline grains is 2 μm or more. Here, the average diameter is obtained by cutting the cross section of the sample after filling it with resin, and averaging the area of ​​the polycrystalline grains that appeared on the cross section, weighted by area. Crystalline silica is expected to have a higher thermal conductivity than amorphous silica, but if the polycrystalline grain size is too small, sufficient thermal conductivity cannot be obtained due to scattering caused by grain boundaries. Therefore, in order to obtain sufficient thermal conductivity, the average diameter of the polycrystalline grain size must be 2 μm or more.

[0022] In the spherical silica particles of the present invention, the polycrystalline grain size (average diameter) is measured by dispersing and filling crystalline powder in an epoxy resin, cutting out a cross section, and using the EBSD (Electron Back Scatter Diffraction Pattern) method.

[0023] In order to verify the effect of improving thermal conductivity by the spherical silica particles of the present invention, a thermal conductive sheet can be prepared by kneading the spherical silica particles of the present invention with a resin, and the thermal conductivity of the sheet can be measured. First, the spherical silica particles are mixed with a silicone resin (CY52-276A / B manufactured by Dow Corning) at a filler ratio of 80% by mass, and the mixture is vacuum degassed to 5 Torr or less and kneaded. The mixture is then molded in a mold. The mold is heated to 120°C, clamped at 6 to 7 MPa, and molded for 40 minutes. The resin composition is removed from the mold and cured at 140°C for 1 hour. After cooling to room temperature, the resin composition is sliced ​​to thicknesses of 1.5, 2.5, 4.5, 6.5, 7.5, and 8.5 mm, and processed into sheet-shaped samples of 2 cm square. The thermal resistance of each sample was measured in accordance with ASTM D5470. The sample is sandwiched between SUS304 blocks and compressed at 0.123 MPa, and the thickness after compression is recorded. The relationship between the thermal resistance value thus obtained and the thickness after compression can be linearly approximated, and the thermal conductivity can be derived from the slope of the linear approximation.

[0024] The spherical silica particles of the present invention have a dielectric loss tangent of 0.0020 or less at 10 GHz as determined by the cutoff cylindrical waveguide method (JIS R1660-1:2004). Without wishing to be bound by a particular theory, it is believed that the spherical silica particles of the present invention have the above-mentioned crystal structure (crystal phase ratio and polycrystalline grain size), and thus have a dielectric loss tangent that is significantly lower than that of amorphous silica, and can also have a high thermal conductivity.

[0025] A method for measuring the dielectric constant and dielectric tangent of the spherical silica particles of the present invention will be described. The measurement is performed using a composite material. The composite material is prepared by using a powder of spherical silica particles and an epoxy resin (YX-4000H manufactured by Mitsubishi Chemical) and kneading 0, 30, 50, and 83 to 89 mass% of the spherical silica particles with respect to the epoxy resin at a temperature of 100°C in a two-roll mill. The kneaded sample was crushed with a mortar and pestle. The crushed sample was filled into a mold (50φ) and set in a press machine. After pressing at 1 MPa for about 1 minute at a molding temperature of 175°C, it was held at 5 MPa for 9 minutes. Then, the mold was transferred to a water-cooled press and cooled for about 10 minutes, and the hardened spherical silica particle-epoxy resin plate (silica-resin plate) was removed from the mold. The prepared silica-resin plate was cut with a peripheral blade and processed to about 10 mm x 10 mm. To change the thickness of the cured silica-resin plate, it was ground using a high-precision surface grinder (SGM-5000 manufactured by Hidewa Kogyo Co., Ltd.) to vary the thickness between 0.2 mm and 1.0 mm. The dielectric properties of the silica-resin composite were measured in the 10 GHz frequency band based on the cutoff cylindrical waveguide method (JIS R1660-1:2004). Based on the relationship between the dielectric loss tangent and composites of 0, 30, 50, and 83 to 89 mass% spherical silica particles with respect to the epoxy resin, the value for 100% spherical silica particles was taken as the dielectric loss tangent of the spherical silica particles.

[0026] The method for producing spherical silica particles according to the present invention will be described.

[0027] The spherical silica particles according to the present invention can be produced by filling silica particle powder (amorphous) produced by a thermal spraying method in the atmosphere into an alumina container and treating the powder in an air atmosphere at a heat treatment temperature range of 800°C to 1600°C for 50 minutes to 16 hours. The preferred heat treatment time is 1 to 12 hours. If the heat treatment time is less than 1 hour, crystallization may not be sufficient, and if the heat treatment time exceeds 12 hours, the manufacturing cost becomes high. In order to promote the crystallization of cristobalite, a small amount of Al is added and the powder is treated at 900°C to 1600°C. The ratio of amorphous and crystalline silica (cristobalite phase and quartz phase) can be controlled by adjusting the treatment temperature and time.

[0028] Here, the amount of Al added is preferably more than 0.5% by mass and not more than 2.0% by mass in terms of oxide. Within this range, sufficient crystallinity can be obtained, and spherical silica particles can be obtained in which the increase in alkali content and the increase in specific gravity caused by Al are suppressed. If it is 0.5% by mass or less, the crystallinity tends to decrease, and if it exceeds 2.0% by mass, the increase in alkali content and the increase in specific gravity become significant, which adversely affects the resin curing properties and tends to make it difficult to apply the particles to mobile devices and in-vehicle applications that require weight reduction.

[0029] In addition, in Patent Documents 1 and 2, the amount of aluminum added is limited to 5000 ppm by mass (0.5% by mass) or less in terms of oxide, and therefore, in order to achieve sufficient crystallization, a heat treatment at a higher temperature and for a longer period of time is required, which may cause particles to easily fuse together.

[0030] When the crystallization of quartz is promoted, a small amount of alkali metal or alkaline earth metal is added and the mixture is treated at 800 to 1150°C, which is a lower temperature than the crystallization temperature of cristobalite, and quartz appears as the main phase. The amount of alkali metal or alkaline earth metal added may be 0.1 to 3 mass% in terms of oxide. If the amount is too small, quartzization is not promoted, and if the amount is too large, the purity of the silica particles decreases. Examples of alkali metals and alkaline earth metals include lithium, sodium, potassium, rubidium, cesium, francium, beryllium, magnesium, calcium, strontium, barium, and radium. From the viewpoint of the efficiency of quartzization promotion, Li and Ca are more preferable. The content of aluminum, alkali metals, and alkaline earth metals can be measured, for example, by atomic absorption spectrometry or ICP mass spectrometry (ICP-MS).

[0031] In one embodiment of the present invention, the ratio of the crystalline quartz phase in the spherical silica particles may be 30% by mass or more. Since cristobalite has a phase transition point between low and high temperature phases at 200-250°C, it effectively undergoes large thermal expansion, which may be an obstacle depending on the application. When such a point is important, it is desirable to make the quartz phase 30% by mass or more. Since the phase transition point between low and high temperature phases of quartz is 500°C or more, it is not an obstacle in practical use. Within this range, spherical silica particles having thermal expansion characteristics suitable for semiconductor packages can be obtained. If it is less than 30% by mass, the thermal expansion caused by the phase transition of the cristobalite phase becomes too large.

[0032] The spherical silica particle (amorphous) powder, which is the raw material of the spherical silica particles of the present invention, can be produced by a thermal spraying method. Specifically, a burner with a tubular structure assembled from a combustible gas supply pipe, a combustion supporting gas supply pipe, and a crushed high-purity silica (quartz) supply pipe is installed at the top of a production furnace, while the lower part of the production furnace is connected to a collection system (the generated powder is sucked in by a blower and collected by a bag filter), and a spherical silica particle (amorphous) powder is produced by thermal spraying using an apparatus. In addition, LPG was supplied from the combustible gas supply pipe and oxygen was supplied from the combustion supporting gas supply pipe to form a high-temperature flame in the production furnace. Crushed silica powder (quartz) was supplied from the silica supply pipe, and the spherical silica powder was collected by a bag filter. The spherical silica particles obtained by thermal spraying can have a circularity of 0.83 or more. Since the higher the circularity, the more improved the fluidity, it is preferable that the circularity is 0.83 or more. By a thermal spraying means, particles with a high circularity can be easily obtained. In order to obtain spherical silica particles with a circularity of 0.83 or more by thermal spraying, it is necessary to melt the raw silica powder and make it spherical, so the flame temperature during thermal spraying must be higher than the temperature at which the silica melts. To obtain spherical silica with a higher circularity, it is desirable for the flame temperature to be 2000°C or higher. Furthermore, when silica particles come into contact with each other during thermal spraying, the particles tend to bond together and form irregular shapes. Therefore, it is desirable to supply the raw material to the flame by dispersing the raw material in the gas flow or by adjusting the supply amount.

[0033] Furthermore, the spherical silica particles of the present invention hardly lose any circularity before or after the heat treatment for crystallization described above, and can maintain the circularity of the spherical silica particles (amorphous) obtained by thermal spraying.

[0034] In this specification, unless otherwise specified, the circularity is measured for 6000 particles of 10um or more size using FPIA-3000 manufactured by Malvern Panalytical. When sizes of 10um or less are also measured, the resolution of the measuring device is generally insufficient, and the circularity may be calculated higher. In that case, the circularity cannot be used as an index of fluidity. Therefore, the circularity is measured for sizes of 10μm or more. First, 10g of powder sample such as silica particles to be measured and 200ml of distilled water are placed in a beaker, and ultrasonic waves are applied using an ultrasonic homogenizer at a frequency of 20 to 30kHz and 150 to 500W for 30 seconds or more to disperse the particles sufficiently. After dispersion, the beaker is left stationary for 1 minute, 180ml of the supernatant side is discarded, and new distilled water is added to make the total volume 200ml. The required amount is taken out from this using a pipette or the like and measured using an optical measuring device. The particle size is defined as the circle equivalent diameter. This is the diameter of a circle having an area equal to the projected area on the measurement image,

number

[0035] In one embodiment of the present invention, there is provided a spherical silica particle mixture comprising 95% by mass or more and 99.9% by mass or less of the spherical silica particles and 0.1% by mass or more and 5% by mass or less of ultrafine particles having an average particle size of 0.1 μm or less. By appropriately blending ultrafine particles of 0.1 μm or less with the spherical silica particles of the present invention, it is possible to improve the filling rate when the spherical silica particles are used as a filler. This is because the ultrafine particles enter the gaps between the spherical silica particles, reducing the volume occupied by the gaps, thereby improving the filling rate. The blending ratio of the spherical silica particles and the ultrafine particles is preferably 95% by mass or more and 99.9% by mass or less of the spherical silica particles, and 0.1% by mass or more and 5% by mass or less of the ultrafine particles. If the ratio of the ultrafine particles is too low, the gaps between the spherical silica particles are not filled, and the filling rate is not improved. If the ratio of the ultrafine particles is too high, the ultrafine particles overflow from the gaps between the spherical silica particles, increasing the overall volume. Here, ultrafine particles refer to spherical silica particles having a particle size of 0.1 μm or less. During the manufacturing process of spherical silica particles, particles having a particle size of 0.1 μm or less (ultrafine particles) are separated, and when the final product is manufactured, a specified amount of ultrafine particles can be mixed. The particle size distribution of the spherical silica particles can also be adjusted. By adjusting the particle size distribution of the crushed silica powder (quartz) used as the thermal spraying raw material, the particle size distribution of the spherical silica particles (amorphous) after thermal spraying can be adjusted. The spherical silica particles obtained by heat treatment for crystallization may have a particle size distribution that is slightly different from that of the spherical silica particles (amorphous), but the particle size distribution of the spherical silica particles of the present invention can be adjusted by predicting the amount of change in the particle size distribution or by sieving in a later process. The silica particles of the present invention may have an average particle size (D50) of 1 to 100 μm. If the average particle size exceeds 100 μm, when used as a filler for semiconductor encapsulation, the particle size may be too coarse to easily cause gate clogging or die wear, and if the average particle size is less than 1 μm, the particles may be too fine to be filled in large quantities. The upper limit of the average particle size is more preferably 50 μm, and even more preferably 40 μm. On the other hand, the lower limit of the average particle size is more preferably 3 μm, and further preferably 5 μm. The average particle size here can be determined by particle size distribution measurement using a wet laser diffraction method (laser diffraction scattering method). The average particle size referred to here is called the median diameter, and is determined by measuring particle size distribution using a laser diffraction method, and the particle size at which the cumulative frequency of the particle size is 50% is defined as the average particle size (D50).

[0036] In this specification, unless otherwise specified, the average particle size relating to the particle size distribution of spherical silica particles, ultrafine particles, etc. is determined by particle size distribution measurement by laser diffraction method, etc. Particle size distribution by laser diffraction method can be measured, for example, by CILAS920 manufactured by CILAS Corporation. The average particle size referred to here is called the median diameter, and the particle size distribution is measured by a method such as laser diffraction method, and the particle size at which the cumulative frequency of the particle size is 50% is defined as the average particle size (D50).

[0037] In addition, one aspect of the present invention provides a composite material of the spherical silica particles and a resin. In order to improve the dielectric properties of a composite material, it is effective to increase the filling rate of the silica filler in the resin composite (filler filling rate) and reduce the amount of resin (e.g., epoxy resin) with poor low dielectric constant properties. In the composite material of the present invention, a filler filling rate of 85% by mass or more and less than 95% by mass can be achieved while maintaining high fluidity. In order to ensure high fluidity, it has been difficult to increase the silica filler filling rate to 85% by mass or more, and it has been limited to less than 85% by mass in the past. However, by appropriately blending ultrafine particles of 0.1 μm or less with the silica particles of the present invention, it is possible to further increase the filling rate. In general, increasing the filler filling rate reduces the fluidity, but by setting the amount of ultrafine particles of 0.1 μm or less to 0.1% by mass or more and 5% by mass or less, it is possible to achieve both high filling and high fluidity. This makes it possible to obtain a composite of silica filler and resin with a low dielectric constant and dielectric loss tangent suitable for high frequencies. However, if the silica filler filling rate exceeds 95% by mass, the amount of resin becomes relatively small, making it difficult to obtain a resin composite.

[0038] In one embodiment of the present invention, the composite material includes the spherical silica particles and a resin. The composition of the composite material will be described. When using the slurry composition to manufacture a resin substrate such as a package substrate or an interlayer insulating film, it is preferable to use an epoxy resin as the resin. The epoxy resin is not particularly limited, but examples thereof include bisphenol A type epoxy resin, bisphenol F type epoxy resin, biphenyl type epoxy resin, phenol novolac type epoxy resin, naphthalene type epoxy resin, and phenoxy type epoxy resin. One of these can be used alone, or two or more types having different molecular weights can be used in combination, or one or more types can be used. Among these epoxy resins, bisphenol A type epoxy resin is particularly preferable from the viewpoint of availability and handling.

[0039] For example, when manufacturing semiconductor-related materials such as package substrates and interlayer insulating films, known resins can be used as the resin for the resin composite composition, but it is preferable to adopt an epoxy resin. The epoxy resin is not particularly limited, but for example, bisphenol A type epoxy resin, bisphenol F type epoxy resin, biphenyl type epoxy resin, phenol novolac type epoxy resin, cresol novolac type epoxy resin, naphthalene type epoxy resin, phenoxy type epoxy resin, etc. can be used. One of these can be used alone, or two or more types having different molecular weights can be used in combination. Among these, from the viewpoint of curability, heat resistance, etc., an epoxy resin having two or more epoxy groups in one molecule is preferable. Specifically, biphenyl type epoxy resins, phenol novolac type epoxy resins, orthocresol novolac type epoxy resins, epoxidized novolac resins of phenols and aldehydes, glycidyl ethers of bisphenol A, bisphenol F, bisphenol S, etc., glycidyl ester acid epoxy resins obtained by reacting polybasic acids such as phthalic acid and dimer acid with epochlorohydrin, linear aliphatic epoxy resins, alicyclic epoxy resins, heterocyclic epoxy resins, alkyl-modified polyfunctional epoxy resins, β-naphthol novolac type epoxy resins, 1,6-dihydroxynaphthalene type epoxy resins, 2,7-dihydroxynaphthalene type epoxy resins, bishydroxybiphenyl type epoxy resins, and epoxy resins into which halogens such as bromine have been introduced to impart flame retardancy, etc. Among these epoxy resins having two or more epoxy groups in one molecule, bisphenol A type epoxy resins are particularly preferred.

[0040] In addition, resins other than epoxy resins can be used in applications other than composite materials for semiconductor encapsulation, such as prepregs for printed circuit boards and various engineering plastics, as resin composite compositions. Specifically, in addition to epoxy resins, silicone resins, phenolic resins, melamine resins, urea resins, unsaturated polyesters, fluororesins, polyamides such as polyimide, polyamideimide, and polyetherimide, polyesters such as polybutylene terephthalate and polyethylene terephthalate, polyphenylene sulfide, aromatic polyesters, polysulfones, liquid crystal polymers, polyethersulfones, polycarbonates, maleimide-modified resins, ABS resins, AAS (acrylonitrile-acrylic rubber-styrene) resins, and AES (acrylonitrile-ethylene-propylene-diene rubber-styrene) resins can be used.

[0041] A known curing agent may be used to cure the resin, and a phenol-based curing agent may be used, such as a phenol novolac resin, an alkylphenol novolac resin, or a polyvinylphenol, either alone or in combination.

[0042] The amount of the phenol-based curing agent blended is preferably such that the equivalent ratio to the epoxy resin (phenolic hydroxyl group equivalent / epoxy group equivalent) is less than 1.0 and is 0.1 or more, thereby eliminating any unreacted phenol curing agent remaining, and improving moisture absorption and heat resistance.

[0043] The amount of spherical silica particles blended in the composite material is preferably large from the viewpoint of heat resistance and thermal expansion coefficient. It is usually appropriate that the amount is 70% by mass or more and 95% by mass or less, preferably 80% by mass or more and 95% by mass or less, more preferably 85% by mass or more and 95% by mass or less, based on the total mass of the composite material. This is because if the amount of silica powder blended is too small, it is difficult to obtain effects such as improving the strength of the sealing material and suppressing thermal expansion, and conversely, if it is too large, segregation due to aggregation of silica powder is likely to occur in the composite material regardless of the surface treatment of the silica powder, and the viscosity of the composite material becomes too high, making it difficult to use it as a sealing material.

[0044] As for the silane coupling agent, any known coupling agent may be used, but those having an epoxy-based functional group are preferred. EXAMPLES

[0045] The present invention will be described with reference to the following examples and comparative examples, but the present invention should not be construed as being limited to the following examples.

[0046] [Examples 1-4] Spherical fused (amorphous) silica particles with an average particle size of 29 μm were prepared by thermal spraying. The calcium and aluminum concentrations in the silica particles were 1 mass% and 0.6 mass% in terms of oxide, respectively, so that calcium oxide was added to the raw powder during thermal spraying. cormorant The silica particles were placed in an alumina container and heat-treated at 1400-900° C. The conditions for each example and the measurement results obtained are shown in Table 1 in detail.

[0047] [Examples 5-8] The same procedure as in Examples 1-4 was repeated except that spherical fused (amorphous) silica particles having an average particle size of 9 μm (the amount of ultrafine particles of 0.1 μm or less added was 3.0 masses) were prepared by a thermal spraying method, and the prepared silica particles were placed in an alumina container and subjected to heat treatment at 1400-900° C. The conditions for each example and the obtained measurement results are shown in detail in Table 1.

[0048] [Comparative Example 1-4] Spherical fused (amorphous) silica particles with an average particle size of 29 μm were prepared by thermal spraying. The calcium and aluminum concentrations in the silica particles were <0.01 mass% and 0.1 mass% in terms of oxide, respectively, so that calcium oxide was added to the raw powder during thermal spraying. cormorant The silica particles were placed in an alumina container and heat-treated at 1400-900° C. The conditions for each comparative example and the measurement results obtained are shown in Table 2 in detail.

[0049] [Comparative Example 5-8] Spherical fused (amorphous) silica particles with an average particle size of 9 μm were prepared by thermal spraying. The calcium and aluminum concentrations in the silica particles were <0.01 mass% and 0.1 mass% in terms of oxide, respectively, so that calcium oxide was added to the raw powder during thermal spraying. cormorant The silica particles were placed in an alumina container and heat-treated at 1400-900° C. The conditions for each comparative example and the measurement results obtained are shown in Table 2 in detail.

[0050] [Examples 3, 9-10, Comparative Example 9] Spherical silica particles were prepared under the same conditions as in Example 3, except for the heat treatment time. The prepared spherical silica particles were filled in a silicone resin at 80% by mass as described above, and the polycrystalline grain size distribution was measured by EBSD of the cross-sectional sample. The thermal conductivity was also measured from a sample cut out from the same sample. Under the conditions of Comparative Example 9, the crystal grains did not grow sufficiently, resulting in a slightly inferior thermal conductivity, but sufficient thermal conductivity was obtained in Examples 3, 9, and 10. Table 3 shows these conditions and the measurement results.

[0051] [Comparative Examples 10-11] The same sprayed silica as used in Example 3 was used with the aluminum concentration changed to 0.4 mass% (Comparative Example 10) and 0.2 mass% (Comparative Example 11) calculated as oxide, and crystallization was carried out under the same heat treatment conditions as in Example 3. As a result, the amorphous ratio was high in Comparative Examples 10 and 11.

[0052]

Table 1

[0053]

Table 2

[0054]

Table 3

[0055]

Table 4

Claims

1. A spherical silica particle comprising a crystalline cristobalite phase and a crystalline quartz phase in a total amount of 60% or more, wherein the average diameter of polycrystalline grains constituting the crystalline cristobalite phase or the quartz phase is 2 μm or more, and wherein the dielectric loss tangent at 10 GHz determined by the cutoff cylindrical waveguide method (JIS R1660-1:2004) is 0.0020 or less.

2. 2. The spherical silica particles according to claim 1, containing more than 0.5% by mass and not more than 2.0% by mass of aluminum, calculated as an oxide.

3. 3. The spherical silica particles according to claim 1, wherein the ratio of the crystalline quartz phase in the spherical silica particles is 30% or more.

4. 4. The spherical silica particles according to claim 1, wherein the circularity of particles having a particle diameter of 10 μm or more among the spherical silica particles is 0.83 or more.

5. A spherical silica particle mixture comprising 95% by mass or more and 99.9% by mass or less of the spherical silica particles according to any one of claims 1 to 4 and 0.1% by mass or more and 5% by mass or less of ultrafine particles having an average particle size of 0.1 μm or less.

6. A composite material comprising a resin and 85% by mass or more and 95% by mass or less of the spherical silica particles according to any one of claims 1 to 4.

Citation Information

Patent Citations

  • Resin composition

    JP2008120877A

  • Silica particle and method of manufacturing the same

    JP2012102016A

  • Spherical crystalline silica particles and method for producing same

    WO2016031823A1

  • Crystalline silica particle material and method for manufacturing same, slurry composition containing crystalline silica particle material, and resin composition containing crystalline silica particle material

    WO2017188301A1

  • Spherical crystalline silica particles and method for producing same

    WO2018186308A1